Integrating Service Learning and Asset-Based Community Development for Sustainable Dengue Prevention: Evidence from Indonesia - Setya Putri Rahayu; Fitria Yuli Dharni; Feby Rahmat Adi Winata; Nur Fazri Jafar Jafar (Transformatif: Jurnal Pengabdian Masyarakat, 2025)
Dengue hemorrhagic fever (DHF) remains a critical public health issue in Indonesia, with rising incidence driven by environmental factors and limited community engagement in preventive practices. This study presents a community-based intervention aimed at strengthening dengue prevention through the use of lemongrass (Cymbopogon nardus) as a natural mosquito repellent. The program adopted a Service Learning (SL) approach integrated with Asset-Based Community Development (ABCD), emphasizing participatory engagement and the utilization of locally available resources. Conducted in Bendungan VII Hamlet, Yogyakarta, the intervention involved 38 community members and was implemented through four stages: community asset mapping, collaborative planning, educational outreach, and hands-on training in producing lemongrass-based mosquito repellent mist. The findings demonstrate a significant improvement in participants’ knowledge and practical competencies. Approximately 90% of participants were able to accurately explain the production process, while 95% successfully produced the repellent independently. Participants also expressed willingness to replicate and disseminate the practice within their community. This study underscores the effectiveness of integrating community empowerment frameworks with eco-friendly health interventions in addressing vector-borne diseases. The use of locally sourced herbal resources not only supports sustainable dengue prevention but also enhances community resilience and self-reliance.